THE CORE CONNECTORS INITIATIVE: DEVELOPMENT OF A YOUTH MENTAL HEALTH PROGRAM - Chou, Fred; Pradhan, Kesha; Huang, Carmen (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2022)
This paper provides an overview of the development and field-test evaluation of a group-based youth mental health promotion program known as the Core Connectors Initiative (CCI). CCI is a program that aims to help youth gain mental health knowledge and peer support competencies, and reinforce positive help-seeking behaviour. The purpose of the study was to evaluate and refine CCI by examining whether it attains its training objectives of mental health literacy, gatekeeper training, and fostering positive youth development, while exploring helpful and unhelpful participant experiences of the program. CCI was field-tested during the latter half of the 2017/2018 school year at 3 different locations: a private school, a community centre, and a public school. Using mixed methods, the evaluation yielded information on the strengths and areas of growth for future program development. The quantitative data were collected from a sample of 29 youth, while the qualitative data were collected from 9 youth using the Enhanced Critical Incident Technique. The converging data highlight the importance of connection, the value of critical mental health literacy, and the importance of clarifying expectations. The lessons learned from implementing this program can be applied to other youth mental health promotion programs.